Strongyloidiasis in Ontario: Performance of diagnostic tests over a 14-month period. Issue 6 (November 2016) - Dong, Michelle Dao; Karsenti, Nessika; Lau, Rachel; Ralevski, Filip; Cheema, Karamjit; Burton, Laura; Klowak, Michael; Boggild, Andrea K.
Abstract: Background: We evaluated the performance of stool microscopy, serology, and real time PCR (qPCR) for the diagnosis of strongyloidiasis at our reference laboratory. Methods: Using a convenience sample of specimens submitted between April 1, 2014 and May 31, 2015, positivity rates and performance characteristics were calculated. Results: During the enrolment period, 17, 933 stool specimens were examined for O&P, 14 of which were positive for Strongyloides larvae. For stool specimens serially positive for larvae, mean duration of larval shedding was 12.7 days following the initial positive specimen, while for sputum and urine, it was 12 and 2 days, respectively. During the enrolment period, 3258 specimens were processed for Strongyloides serology, 200 of which were reactive (6.1%), 210 indeterminate (6.5%), and 2848 non-reactive (87.4%). qPCR was positive in 11 of 12 (91.7%) stool specimens containing larvae, and negative in all stool specimens without larvae by microscopy. There was no cross-reactivity of Strongyloides -specific qPCR to other stool protozoa or helminths. Conclusions: In the absence of immunosuppression, larval burden in strongyloidiasis is low, limiting the utility of microscopy, and favoring serologic testing. However, false negative serology can occur in those with hyperinfection necessitating a combined diagnostic approach. qPCR was insufficiently sensitive to replace microscopy for detection of larvae.